2007
DOI: 10.1051/0004-6361:20065041
|View full text |Cite
|
Sign up to set email alerts
|

A search for OB stars in the field of the galactic OB association Bochum 7

Abstract: Context. The presence of a Wolf-Rayet star, WR12, at α = 8 h 44 m 47.2 s , δ = −45 • 58 55.5 (J2000.0), triggered the search for a surrounding OB association now known as Bochum 7. Several papers have dealt with the existence of Bo 7, but none actually included spectral types of the stars. To assure the spectral types of members of the association, it is essential to have spectral images of them. Aims. In this paper we present previously unpublished spectra of OB stars over a 30 arcmin field covering the estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…The E(B − V ) colour excess amounts to 0.20-0.45 mag for Vel OB1 and 0.75-1.05 mag for Bochum 7. From the U BV observations of practically the same field made by Corti et al (2007) the following ranges of E(B −V ) can be estimated: 0.25-0.48 mag for Vel OB1 and 0.58-1.0 mag for Bochum 7, in good agreement with Sung et al (1999). It is obvious that the spread of reddening in our small field will be much smaller.…”
Section: Colour-colour and Colour-magnitude Diagramssupporting
confidence: 86%
See 2 more Smart Citations
“…The E(B − V ) colour excess amounts to 0.20-0.45 mag for Vel OB1 and 0.75-1.05 mag for Bochum 7. From the U BV observations of practically the same field made by Corti et al (2007) the following ranges of E(B −V ) can be estimated: 0.25-0.48 mag for Vel OB1 and 0.58-1.0 mag for Bochum 7, in good agreement with Sung et al (1999). It is obvious that the spread of reddening in our small field will be much smaller.…”
Section: Colour-colour and Colour-magnitude Diagramssupporting
confidence: 86%
“…As mentioned above, the field we observed contains stars from at least two OB associations, Vel OB1 and Bochum 7. Sung et al (1999) and Corti et al (2007) observed much larger field than we did, 30 × 30 , roughly covering the area shown in Fig. 1.…”
Section: Colour-colour and Colour-magnitude Diagramssupporting
confidence: 79%
See 1 more Smart Citation
“…(Corti 2005). In the above listing the prefix LS stands for stars listed in the LSS Catalogue (Stephenson & Sanduleak 1971), while CBN indicates those stars identified by Corti et al (2007). Following the guidelines of the IAU, CBN stars are identified using the capitalized first letters of the last names of the authors followed by GALACTIC LAT.…”
Section: Was the Birth Of Bochum 7 Triggered By Gs263-02+45?mentioning
confidence: 99%
“…For ionizing stars of nearby H II regions, located in the Milky Way and the Magellanic Clouds, the effective temperature can be directly estimated by using their photometric and spectrometric data (e.g. Massey et al 2005Massey et al , 2009Corti et al 2007;Sota et al 2011;Morrell et al 2014;Walborn et al 2014;Lamb et al 2016;Evans et al 2015;Mohr-Smith et al 2017;Martins & Palacios 2017;Markova et al 2018). However, for the majority of the distant ionizing massive stars, T eff can only be indirectly estimated, e.g.…”
Section: Introductionmentioning
confidence: 99%